Antimicrobial activity of secondary metabolites of Aspergillus fumigatus sensu stricto on clinical strains of Staphylococcus aureus and Streptococcus pneumoniae - Sanchez-Perez, Jorge A. (2020)
Introduction. The antibiotic resistance of Gram positive bacteria is a serious public health problem where some palliative measures can be found in the antimicrobial principles of filamentous fungi. Objective. To evaluate the antimicrobial activity of secondary metabolites of a clinical isolation of Aspergillus fumigatus on clinical strains of Staphylococcus aureus and Streptococcus pneumoniae. Methods. The liquid fermentation of A. fumigatus was carried out in a liquid broth sulfate, potato and dextrose; using ethyl acetate for the extraction of secondary metabolites. The antimicrobial activity considered as a halo greater than 6 mm was evaluated using the diffusion disk methodology. Results. A mean of 24,02 ± 2,51 mm and 23,62 ± 4,68 mm was obtained on sensitive and resistant Staphylococcus aureus, respectively. For Streptococcus pneumoniae sensitive and non-susceptible, the means were 25,82 ± 4,05 mm and 26,5 ± 5,39 mm, respectively. Conclusions. The crude extract of A. fumigatus has secondary metabolites of alkaloid nature and unsaturated sterols with antimicrobial activity.